(untitled) (Bangladesh Critical Care Journal, 2024)
Introduction: Right Ventricular (RV) function is a strong predictor of outcome in many Cardiovascular Diseases, but its significance is often neglected. Right Ventricle (RV) dysfunction may be secondary to Left Ventricle (LV) dysfunction as a consequence of “Ventricular Interdependence. Tricuspid Annular Plane Systolic Excursion (TAPSE) is an Echocardiographic measure that allows us to assess Right Ventricular systolic function and it correlates well with reference techniques like Cardiac Magnetic Resonance Imaging. Echocardiographic recording of the Tricuspid Annular Plane Systolic Excursion (TAPSE) has been recommended for assessing Right Ventricular function in cardiac patients. As RV dysfunction is associated with high in-hospital morbidity and mortality, early reorganization of RV dysfunction is warranted in patients with or without LV dysfunction. Objective: Our objective was to demonstrate the relationship of TAPSE, as a predictor of RV Systolic Function with Left Ventricular Systolic Function. Method: This was a cross –sectional study in patients undergoing comprehensive Transthoracic Echocardiography for any indication. From April 2022 to March 2023 we prospectively enrolled 100 adult (from 30 to age 103years) of both sexes who presented to the Cardiology Clinic of LABAID Cardiac Hospital. We performed a complete Transthoracic Echocardiography study. Assessed LV systolic function by conventional method. We additionally measured TAPSE in 2-dimensional M-mode Echocardiograms from the apical 4- chamber view, positioning the cursor on the lateral Tricuspid Annulus near the free RV wall and aligning it as close as possible to the apex of the heart. The mean values were taken by at least 2 measurements for reducing inter-observer and intra-observer variability’s. Values of TAPSE as a predictor of RV Systolic Function were correlated with Left Ventricular Systolic Function. Patients with confirmed congenital & Valvular heart disease were excluded. Results: Mean TAPSE values were (19.15±3.87mm) irrespective of LVEF, with no significant differences between sexes, (18.45±3.801 mm) in male , (19.94±3.853 mm) in female (P=.056). TAPSE value was (22.00±1.581 mm) in person with normal LVEF & (16.77±2.455 mm) in person with reduced LVEF (P<.001). A statistically significant positive correlation of LVEF (r=.813) and significant negative correlation of EPSS (r=-.639) were observed with TAPSE (p<0.001). But no significant correlation of TAPSE was found between age (r=-.185), gender (r=.192) & RVIDd (r= -.063) (p >0.05). Multivariate analysis confirmed these correlations and the interactions between variables. Graph of estimated population-based TAPSE values adjusted by LV function was provided. Conclusion: We determined the values of TAPSE in patients with or without LV systolic dysfunction and assessed relationship of these values with LVEF. TAPSE is predictive of RV Systolic function & correlated significantly with LV systolic function. The TAPSE measurement is simple & reproducible. This observation could guide decision making in daily clinical practice. Bangladesh Crit Care J March 2024; 12 (1): 11-17